Pengaruh Paparan Karbon Monoksida Dan Karakteristik Individu Terhadap Kelelahan Kerja Pada Pekerja Pengasapan Ikan di Kampung Ikan Asap Penatarsewu Kabupaten Sidoarjo - Merditha Tri Cahyani; Asteria Narulita Pramana (Indonesian Journal of Health Community, 2022)
Work fatigue is one of health and safety problems which can be risk factor for workplace accidents. There are many factors that cause work fatigue, like age, gender, work load, working period, and carbonmonoxide exposure. The objective of this study was to identity the carbon monoxide exposure in blood and workers characteristic on work fatigue in the fum fish village Penatarsewu Sidoarjo Regency. The research was using cross sectional design with 42 samples. Work fatigue was quantified with reaction timer carbon monoxide effect with measuring COHb level in blood, work load with fingertrip oximeter, and workers characteristic were collected through interview with questionnaires. Study was analyzed with multivariate logistic regression through SPSS. The research shows analysis suggests that age and sex aren’t significantly related to work-related fatigue, while employment period, work load and Carbon Monoxide exposure are significantly related to work-related fatigue. The result of multivariate analysis shows that work load, employment period and Carbon Monoxide exposure are significantly related to work-related fatigue. Work load is the dominant variable for work-related fatigue. Workers having heavy work load are exposed to work-related fatigue 9 times higher compared to those with light work load.